Impact of green revolution in selected countries of South Asia and South-east Asia. - Center on Integrated Rural Development for Asia and the Pacific; Food and Agriculture Organization of the United Nations (Dhaka : Centre on Integrated Rural Development for Asia and the Pacific, 1994)
Overview of the major findings of two studies carried out by the Center on Integrated Rural Development for Asia and the Pacific, with the financial assistance from the Food and Agriculture Organization, in India and the Philippines during December 1993.
Includes bibliographical references.
Keywords: Agriculture -- Economic aspects -- India; Agriculture -- Economic aspects -- Philippines; Green Revolution -- Economic aspects -- Southeast Asia